The Impact of Single Session Intermittent Theta-Burst Stimulation over the Dorsolateral Prefrontal Cortex and Posterior Superior Temporal Sulcus on Adults with Autism Spectrum Disorder - Ni, Hsing-Chang; Hung, June; Wu, Chen-Te; Wu, Yu-Yu; Chang, Chee-Jen; Chen, Rou-Shayn; Huang, Ying-Zu (Frontiers in Neuroscience, 2017)
Intermittent theta burst stimulation (iTBS), a patterned repetitive transcranial magnetic stimulation, was applied over the posterior superior temporal sulcus (pSTS) or dorsolateral prefrontal cortex (DLPFC) to explore its impact in adults with autism spectrum disorder (ASD). Among 25 adults with ASD, 19 (mean age: 20.8 years) completed the randomized, sham-controlled, crossover trial. Every participant received iTBS over the bilateral DLPFC, bilateral pSTS and inion (as a sham control stimulation) in a randomized order with a 1-week interval. Neuropsychological functions were assessed using the Conners’ Continuous Performance Test (CCPT) and the Wisconsin Card Sorting Test (WCST). Behavioral outcomes were measured using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and the Social Responsiveness Scale (SRS). In comparison to that in the sham stimulation, the reaction time in the CCPT significantly decreased following single DLPFC session (p=0.04, effect size = 0.71) while there were no significant differences in the CCPT and WCST following single pSTS session. Besides, the results in behavioral outcomes were inconsistent and had discrepancy between reports of parents and patients. In conclusion, a single session of iTBS over the bilateral DLPFC may alter the neuropsychological function in adults with ASD. The impacts of multiple-sessions iTBS over the DLPFC or pSTS deserve further investigations.